PENENTUAN PRIORITAS SARANA PASCAPANEN JAGUNG UNTUK MENURUNKAN KEHILANGAN HASIL DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Deasy Fitriani; Rokhani Hasbullah; Ridwan Rachmat (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2015)
Maize is one of the important sources of feed ingredients, an appropriate postharvest facilities can reduce a quantitative losses in maize postharvest handling. The objective of this study was formulating the criteria and sub criteria in having a decision making about the priorities of postharvest facility that can reduce quantitative losses.This study utilized the Analytical Hierarchy Process (AHP) method and obtained data was analyzed using software Expert Choice, as a decision making program. Experts’ and potential respondents’ judgments have the inconsistency less than 10%. The most important actor under the goal is government. Furthermore, the most important criteria is the quality and the subcriteria is SNI. Dryer followed by corn sheller are the prioritized alternatives in order to reduce postharvest quantitative losses of maize.